Comparative genomic analysis of human GLI2 locus using slowly evolving fish revealed the ancestral gnathostome set of early developmental enhancers. Issue 5 (7th January 2021) - Ali, Shahid; Arif, Irum; Iqbal, Ayesha; Hussain, Irfan; Abrar, Muhammad; Khan, Muhammad Ramzan; Shubin, Neil; Abbasi, Amir Ali
Abstract: Background: The zinc finger‐containing transcription factor Gli2, is a key mediator of Hedgehog (Hh) signaling and participates in embryonic patterning of various organs including the central nervous system (CNS) and limbs. Abnormal expression of Gli2 can impede the transcription of Hh target genes through disruption of proper balance between Gli2 and Gli3 functions. Therefore, delineation of enhancers that are required for complementary roles of Glis would allow the interrogation of those pathogenic variants that cause gene dysregulation, and a corresponding abnormal phenotype. Previously, we reported tissue‐specific enhancers for Gli family including Gli2 through direct tetrapod‐teleost comparisons. Results: Here, we employed the sequence alignments of slowly evolving spotted gar and elephant shark and have identified six novel conserved noncoding elements in human GLI2 containing locus. Zebrafish‐based transgenic assays revealed that combined action of these autonomous CNEs reflects many aspects of Gli2 specific endogenous transcriptional activity, including CNS and pectoral fins. Conclusion: Taken together with our previous findings, this study suggests that Hh‐signaling controlled deployment of Gli2 activity in embryonic patterning arose in the common ancestor of gnathostomes. These GLI2 specific cis ‐regulatory modules will help to identify DNA variants that probably reside outside of coding intervals and are associated with congenital anomalies. Key Findings: We performed a phylogenetic footprint analyses of human GLI2 containing locus by incorporating relatively slowly evolving gar and elephant shark genomes and have identified multiple novel conserved non‐coding elements (CNEs) that were not predicted by direct human‐teleostcomparisons. Comparative analyses suggest that majority of the GLI2 associated CNEs identified in the present data and reported previously arose in the common ancestor of gnathostomes but lost in teleosts, presumably because of fast teleost sequence evolution. Functional testing of GLI2 associated CNEs by employing zebrafish based transgenic reporter assays revealed their tissue specific cis‐regulatory potential that corresponds with the results based on whole‐mount in situ hybridization analysis of gli2 mRNA in zebrafish. The delineated set of GLI2 associated enhancers can be further interrogated to determine their role in canonical Hh signaling, gene dysregulation, and a corresponding congenital anomaly.